Characterization Analysis: Cinderella in Grimm's Fairy Tales (Jacob & Wilhelm Grimm) and Cinderella (Grimm's Fairy Tales 2003) - S. Vanya Ides Ramadhani (Pusat Riset dan Inovasi Nasional, 2023)
The present article aims to identify the characterization of Cinderella in two different versions of the fairy tale: